Interactive Urban Play to Encourage Active Mobility: Usability Study of a Web-Based Augmented Reality Application - Oduor, Michael; Perälä, Timo (Frontiers in Computer Science, 2021)
Owing to increasing cases of sedentary lifestyles and their negative impact on health, practical solutions are needed to address the physical and mental wellbeing of citizens and to enhance their standard of living. Among the problems are premature mortality rates caused by physical inactivity, which leads to chronic diseases. Innovative solutions are needed to address many of the problems that we face as a society. Location-based games have been identified as effective solutions for increasing physical activity, enhancing social interaction, and exploration in urban environments. In this pilot study, we explore how to encourage active mobility (walking and cycling) through urban play by integrating technology into the built environment. We examined the usability of a web-based augmented reality application in providing interactive experience to users as they explored the urban environment looking for tasks. Overall, participants’ perceptions of the usability of the application were positive; they enjoyed how the application revealed the tasks at each location and all the checkpoints at the different locations had at least a couple of visitors. We present limitations and future research directions.